Fueling Rural: The Unseen Forces of Family Background and Psychological Factors on Youth Entrepreneurship - Muhammad Dharma Tuah Putra Nasution; Ramadhan Harahap; Irawan Irawan; Aulia Ramadhan Tanjung (UNIVED Press, 2024)
Understanding entrepreneurial intentions among rural youth is crucial for fostering economic development; however, this demographic remains underrepresented in entrepreneurship research. This study explores the impact of entrepreneurial family backgrounds and psychological factors-such as self-efficacy, risk-taking propensity, need for achievement, and locus of control-on entrepreneurial intentions among rural youth in Deli Serdang, North Sumatera, Indonesia. A quantitative approach was utilized, employing a cross-sectional survey with data collected from a random sample of 217 rural youth through a structured questionnaire administered in person. Data analysis was conducted using partial least squares structural equation modeling (PLS-SEM). The results demonstrate that both entrepreneurial family background and psychological factors significantly influence entrepreneurial intentions. Specifically, having an entrepreneurial family background positively affects these intentions, while psychological factors also play a significant role. The study validates the research instruments and offers valuable insights into how familial and psychological influences shape entrepreneurial aspirations in rural contexts, reinforcing theories related to entrepreneurial self-efficacy, motivation, and psychological capital. For policymakers, the findings highlight the importance of supporting family-based entrepreneurial initiatives and integrating family involvement into entrepreneurial education. Educators are encouraged to incorporate psychological training to cultivate traits such as self-efficacy and resilience, while practitioners should develop supportive environments that leverage both familial and psychological resources. The study’s limitations include its focus on rural youth, which may restrict generalizability, reliance on self-reported measures, and the lack of exploration into underlying mechanisms or longitudinal effects. Future research should address these limitations by incorporating diverse populations, utilizing objective measures, and examining long-term impacts.